IMPLEMENTASI ALGORITMA APRIORI SEBAGAI ALTERNATIF STRATEGI PROMOSI UNIVERSITAS PGRI MAHADEWA INDONESIA - Ida Ayu Putu Febri Imawati; Budhya Wirandha Gupta; I Kadek Juni Arta; I Wayan Dika (Jurnal Manajemen dan Teknologi Informasi, 2025)
UPMI Bali is a new campus, so campus promotion is still very much needed to increase prospective new students at UPMI Bali. By utilizing available data, the campus can determine effective campus promotion strategies using data mining. The data system will be built using the Association Rules technique. Association Rules is a data mining method to find frequently occurring association patterns in data. This method is popular because it is often used to analyze shopping carts. The rules formed will be in the form of "If-Then" in a transaction. Using the apriori algorithm generally involves finding frequent itemsets from a sales transaction database through several iteration stages. The association patterns formed with a minimum support value of 10% and confidence of 50% produced 18 association rules, with the strong rule obtained being Lecturer and Denpasar with a support value of 22% and confidence of 50%. Thus, if students know about the UPMI campus reference from a Lecturer, then these students are from Denpasar.